Ekologi Media Sosial Dan Wacana Makan Bergizi Gratis (MGB) Di Indonesia: Analisis Transformasi Ruang Publik, Identitas, Dan Pola Kognisi Digital - Muhibuddin, Muhibuddin; Solihin, Muchtar; Munir (AdZikra : Jurnal Komunikasi & Penyiaran Islam, 2025)
This article examines the discourse of Free Nutritious Meals (FNM) in Indonesia through the lens of media ecology, focusing on the transformation of public space, digital identity, and cognitive patterns in the social media era. Using a qualitative approach and critical discourse analysis of social media content, this study reveals how digital platforms such as Twitter, Instagram, and TikTok not only serve as information channels but also shape symbolic ecosystems that influence how society perceives issues of health, nutrition, and public policy. The findings indicate that social media has shifted the authority of nutrition discourse from experts and the government to the public, creating participatory dynamics that are vulnerable to misinformation and polarization. Digital identity is constructed through personalized narratives and visual campaigns, while public cognition is driven toward preferences for short, emotional, and viral content. This article offers policy recommendations based on ecological media literacy and sustainable platform design to support inclusive and evidence-based FNM discourse.